Acute kidney injury in an extremely low birth weight infant with nephrolithiasis: a case report - Garunkštienė, Rasa; Vaitkevičienė, Rimutė; Paulavičienė, Ieva; Drazdienė, Nijolė; Čerkauskienė, Rimantė (Acta medica Lituanica, 2019)
Acute kidney injury is associated with mortality of very low birth weight infants and reduces their survival regardless of other factors. The kidneys in the extremely preterm infants are very immature and susceptible to environmental factors. Clinical conditions and medications are risk factors for acute kidney injury in these patients. Nephrolithiasis in preterm infants is an extremely rare phenomenon that usually manifests as a complication of nephrocalcinosis. This is a case report that describes several episodes of acute kidney injury in the first two months of age in an extremely low birth weight infant with kidney stones in the background. The main causes that led to acute kidney injury in this patient were persistent ductus arteriosus, sepsis and captopril. At one month of age, ultrasound detected calcinates in the right kidney. Within two weeks a large number of linear stones formed across the collecting duct system. Small calcinates still remained in the right kidney when the girl was half a year of the corrected age. The evaluation of a neonate who develops acute kidney injury requires a systematic approach. Early identification of the emerging risk factors and prevention of nephrolithiasis along with effective treatment can reduce the risk of developing acute kidney injury in very low birth weight infants.
Keywords: acute kidney injury; nephrolithiasis; preterm infant